"Imago expandit splendorem suum". Hildegard of Bingen’s Visio-Theological Designs in the Rupertsberg Scivias Manuscript - Campbell, Nathaniel M. (Eikón / Imago, 2013)
A significant point of contention within studies of the twelfth-century visionary saint and Doctor of the Church, Hildegard of Bingen, is the question of her role in the production of the illuminated Scivias manuscript known as the Rupertsberg Codex. While current German scholarship has tended to preclude Hildegard’s hand, pre-war German scholars, who had access to the original manuscript before it was lost, and most modern Anglophone scholars have argued more or less strongly for Hildegard’s influence on the design. This paper argues for Hildegard’s direction of the images based on their function as a theological discourse refracting the text. The images are not ancillary to or derivative of the work; they are integral to it. A key area of the manuscript design that reveals these authorial interventions is the color scheme. The use of certain colors, such as green and red, that have particular meanings in Hildegard’s symbolic vocabulary—even when at odds with the colors described in the recorded vision text—reveals the theological place of each image within Hildegard’s perception of salvation history. Furthermore, the extensive use of silver, gold, and blue in the manuscript can be understood both through Hildegard’s likely use of actual jewelry that contained enamel work and those metals, and through the theological meanings with which Hildegard imbues the metallic pigments. Such visual markers invested with theological significance thus argue for Hildegard’s design of the manuscript and aid the viewer- reader in interpreting the complex visual allegories at work in Hildegard’s often enigmatic visions. Finally, they reveal the dynamic ways in which Hildegard used the images to emphasize her theological insights into the feminine divine and its connection especially to her and her community as virgin members of a virgin Church.